Neuroprotective Effects of Apple‐Derived Drinks in a Mice Model of Inflammation. Issue 2 (23rd December 2019) - Alvariño, Rebeca; Alonso, Eva; Alfonso, Amparo; Botana, Luis M.
Abstract : Scope: Fruit‐derived drinks consumption is considered beneficial due to the antioxidant and neuroprotective effects of polyphenols separately, but studies including their total constituents are scarce. In this work, the antioxidant and anti‐inflammatory neuroprotective effects of apple‐derived beverages are determined in a mouse model of lipopolysaccharide (LPS)‐induced inflammation. Methods and results: Preliminary antioxidant and neuroinflammatory experiments are carried out with 15 drink polyphenolic extracts in SH‐SY5Y and BV2 cells, using H2 O2 as pro‐oxidant and LPS as pro‐inflammatory stimulus, respectively. Extracts improve antioxidant systems functioning and present neuroprotective mitochondrial‐related effects. In microglia, extracts reduce reactive oxygen species and modulate cytokine release. To better mimic human consumption, four concentrated dealcoholized apple‐derived drinks (three ciders and apple juice) are supplied to mice for 7 days in substitution of drinking water. Mice treated with beverages present reduced brain oxidative stress and inflammatory markers after LPS injection. Interestingly, genetic expression of antioxidant enzymes and glutathione levels are also greatly augmented after drink intake. Conclusion: The results confirm the antioxidant and anti‐inflammatory‐mediated neuroprotective properties of apple‐derived drinks, suggesting that their consumption could be a good approach for prevention of neurodegenerative disorders. To the authors' knowledge, this is the first description of cider neuroprotective effects. Abstract : Fruit‐derived drink consumption is considered beneficial due to their great content of polyphenolic compounds. The in vitro neuroprotective activity of 15 drink polyphenolic extracts is evaluated, showing antioxidant and anti‐neuroinflammatory properties. Then, four apple‐derived beverages are chosen to determine their potential in a mouse model of inflammation. Drinks decrease brain oxidative stress, upregulate antioxidant gene expression, and reduce inflammation.